Kasaysayan ng Filipinas at mga institusyong Filipino - Gripaldo, Eden M.; Boquiren, Rowena R.; Miranda, Evelyn A.; Jose, Ricardo T.; Ignacio, Violeta S.; Ambrosio, Dante L.; Sanchez, Phoebe Sue U.; Talde, Daniel C.; Funtecha, Henry L.; Diestro, Dwight A.; Karganilla, Bernard Leo M.; Mata, Roberto C. (Sentro ng Wikang Filipino, 2003)
History of the Philippines and the Philippine institutions from prehistoric era until the present time.